Metformin monotherapy in youth with recent onset type 2 diabetes: experience from the pre-randomization run-in phase of the TODAY study - Laffel, Lori (2012)
BACKGROUND: TODAY (Treatment Options for type 2 Diabetes in Adolescents and Youth) is a federally-funded multi-center randomized clinical trial comparing three treatments of youth-onset type 2 diabetes. OBJECTIVE: To describe the experience of youth participating in a 2–6 month run-in period in preparation for randomization into TODAY. SUBJECTS: An ethnically diverse sample of 927 youth, 65.4% female, aged 13.7±2.0 years old, with type 2 diabetes for a median of 2 months (0.7–7.8 months, 25(th)-75(th) percentiles). METHODS: A run-in period was conducted to achieve HbA1c <8% with metformin monotherapy and diabetes education, and to evaluate adherence to pill taking, visit attendance, and other procedures. RESULTS: At entry, mean BMI and z-BMI were 35.6±7.7 and 2.3±0.4, respectively, mean HbA1c was 7.7±2.2%, only 42.5% were on a hypoglycemic treatment, and 35.6% had HbA1c ≥8%. Co-morbid conditions were common; 18.8% had hypertension, 24.2% had elevated cholesterol, and 6.5% had abnormal liver enzymes. After a median 71 days of run-in, 90.9% had HbA1c <8%, 77.9% had HbA1c <7%, and 46.4% had HbA1c <6%. Of the 772 youth achieving the target HbA1c <8%, 704 (91.2%) were randomized; non-adherence to metformin treatment was the main cause for non-randomization. Youth proceeding to randomization decreased weight by 0.68 kg and HbA1c by 1.45% compared to a weight gain of 0.71 kg and HbA1c decrease of 0.74% in the non-randomized youth (p=0.01 in both cases). Change in z-BMI was not significantly different between the two groups, however. CONCLUSIONS: Most youth with recent onset type 2 diabetes can achieve target HbA1c <8.0% with short-term metformin monotherapy and standard diabetes education.